Narrative descriptions should replace grades and numerical ratings for clinical performance in medical education in the United States - Hanson, Janice L.; Rosenberg, Adam A.; Lane, J. Lindsey (Frontiers in Psychology, 2013)
Background: In medical education, evaluation of clinical performance is based almost universally on rating scales for defined aspects of performance and scores on examinations and checklists. Unfortunately, scores and grades do not capture progress and competence among learners in the complex tasks and roles required to practice medicine. While the literature suggests serious problems with the validity and reliability of ratings of clinical performance based on numerical scores, the critical issue is not that judgments about what is observed vary from rater to rater but that these judgments are lost when translated into numbers on a scale. As the Next Accreditation System of the Accreditation Council on Graduate Medical Education (ACGME) takes effect, medical educators have an opportunity to create new processes of evaluation to document and facilitate progress of medical learners in the required areas of competence. Proposal and initial experience: Narrative descriptions of learner performance in the clinical environment, gathered using a framework for observation that builds a shared understanding of competence among the faculty, promise to provide meaningful qualitative data closely linked to the work of physicians. With descriptions grouped in categories and matched to milestones, core faculty can place each learner along the milestones’ continua of progress. This provides the foundation for meaningful feedback to facilitate the progress of each learner as well as documentation of progress toward competence. Implications: This narrative evaluation system addresses educational needs as well as the goals of the Next Accreditation System for explicitly documented progress. Educators at other levels of education and in other professions experience similar needs for authentic assessment and, with meaningful frameworks that describe roles and tasks, may also find useful a system built on descriptions of learner performance in actual work settings. Conclusions: We must